Universal Thermal Climate Index in Russia - V. Vinogradova V.; В. Виноградова В. (Izvestiya Rossiiskoi akademii nauk. Seriya geograficheskaya, 2019)
The paper uses the universal thermal climate index (UTCI) to estimate the bioclimate in Russia, initiated by the Commission of the International society of Biometeorology. The UTCI index can be described as equivalent environment temperature (°C), which provides the same physiological impact on humans as the actual environment. Assessment of bioclimatic conditions is shown for the territory of Russia in the period of modern climate change (2001-2015). Cold stress conditions (from low to extreme) were observed in the almost all territory of Russia for about 8-11 months a year. During the rest of the year, the conditions are neutral or comfortable. The period of extreme and very high cold stress is reduced during the modern climate warming (compared to the period 1961-1990), especially in the Arctic, in the European part of Russia, in Western and Eastern Siberia. At the same time, the period with neutral and comfortable thermal conditions increases. В работе использован универсальный индекс теплового комфорта (UTCI) для оценки биоклимата на территории России, инициированный Комиссией Международного общества биометеорологии. Индекс UTCI можно охарактеризовать как эквивалентную температуру окружающей среды (°C), которая оказывает такое же физиологическое воздействие на человека, как и фактическая окружающая среда. Оценка биоклиматических условий показана для территории России в период современного изменения климата (2001—2015 гг.). Условия холодного стресса (от низкого до экстремального) наблюдались почти на всей территории России примерно от 8 до 11 месяцев в году. В течение оставшейся части года условия нейтральные или комфортные. Период экстремального и очень высокого холодного напряжения сокращается во время современного потепления климата (по сравнению с периодом 1961—1990 гг.), особенно в Арктике, на европейской территории России, в Западной и Восточной Сибири. В то же время увеличивается период с нейтральными и комфортными тепловыми условиями.